EFFECT OF NET-MATERIALS ОN THE SPECTRAL RADIANCE FACTOR OF THE OBJECTS FOR DIFFERENT VIEWING ANGLES - S. O. Jamal; I. M. Tsykman; Y. V. Belyaev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Methods are described for experimental studies of the spectral parameters of the reflected radiation from the surface of various materials. The methods of data processing are presented. The results of the determination of the spectral radiance factor of the reflected light materials for different viewing angles are shown.